Effect of bicarbonate on growth of the oleaginous microalga Botryococcus braunii (International Journal of Plant Biology, 2019)
The effect of bicarbonate, produced by the enzymatic hydration of CO2 from postcombustion fumes, was investigated on Botryococcus braunii growth. The NaHCO3, supplied to cultures in the role of inorganic carbon source is proposed as a more eco-sustainable alternative to gaseous CO2. The salt was provided to the cultures at the final concentration of 0.5-1.5-2.5 g L- 1. The growth rate was considered for specific time intervals (T0-T5, T5-T10 and T0- T10) showing values significantly higher in the culture supplemented with 2.5 g L-1 bicarbonate. The doubling times were also considered in all experimental cultures showing a faster doubling for the period T0÷T5. The increase in pH drives the increase in growth in the experimental conditions in which the salt was added. The results suggest that bicarbonate is able to promote the algal growth, therefore it can be considered a valid alternative to CO2 gas.